Answers

  • Brainly User
2015-09-02T23:22:50+08:00

This Is a Certified Answer

×
Certified answers contain reliable, trustworthy information vouched for by a hand-picked team of experts. Brainly has millions of high quality answers, all of them carefully moderated by our most trusted community members, but certified answers are the finest of the finest.
Given the roots, the equation is:
     x² - (sum of the roots)x + (product of roots) = 0

Example 1:  roots 3 and -5
    x² - (3 + -5)x + (3)(-5) = 0
   x² - (-2)x + (-15) = 0
  Equation:  x² + 2x - 15 = 0

Example 2:  roots -4, -1
   x² - (-4 + -1)x + (-4) (-1) = 0
   x² - (-5)x + (4) = 0
   x² + 5x + 4 = 0

Example 3:  roots √2, -√2
  x² - (√2 +  -√2)x + (√2) (-√2) = 0
  x² -  0x + (- √4) = 0
  x² + (-2) = 0
  x² - 2 = 0

You can do the next two examples.  Try the roots 4 and 7;  5 and 2
You can do it :-)
1 5 1